2016
DOI: 10.1016/j.schres.2016.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive insight and objective cognitive functioning in schizophrenia

Abstract: Neurocognitive impairment is a core component of schizophrenia affecting everyday functioning; the extent to which individuals with schizophrenia show awareness of neurocognitive impairment (neurocognitive insight) is unclear. This study investigated neurocognitive insight and examined the cross-sectional relationships between neurocognitive insight and objective neurocognition and functional capacity performance in a large outpatient sample. 214 participants with schizophrenia-spectrum disorders completed mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
19
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 56 publications
8
19
0
3
Order By: Relevance
“…These results are consistent with recent studies focusing on "neurocognitive insight" in schizophrenia, i.e. awareness into cognitive deficits (4248). These studies reported indeed that the lack of insight on psychiatric symptoms (49) could be extended to cognitive impairments.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with recent studies focusing on "neurocognitive insight" in schizophrenia, i.e. awareness into cognitive deficits (4248). These studies reported indeed that the lack of insight on psychiatric symptoms (49) could be extended to cognitive impairments.…”
Section: Discussionsupporting
confidence: 93%
“…negative symptoms), and cognitive complaint in the clinical group. Regarding psychoaffective factors this is in accordance with some (20,21,26,34) but not all studies on this subject (35,36) in schizophrenia. In our study, and similarly to the study of Bayard et al (26) we used the Beck depression Inventory 2 which is a self-rated measure of depression whereas Potvin et al (36) for example used the Calgary Depression Scale for Schizophrenia which consist on a semi-structured interview (37).…”
Section: Discussionsupporting
confidence: 91%
“…negative symptoms), and cognitive complaint in the clinical group. Regarding psychoaffective factors this is in accordance with some ( 20 , 21 , 26 , 34 ) but not all studies on this subject ( 35 , 36 ) in schizophrenia. In our study, and similarly to the study of Bayard et al.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Those who are better aware of their deficits are not associated with a lower use of treatment, nor with a lesser deterioration of executive function. But they do have better results in the rehabilitation of some cognitive domains, in adherence to treatment and in their functional capacity [41,42].…”
Section: Cognitive Deficit In Schizophreniamentioning
confidence: 99%